Śaśāṅka : Rākhaladāsa Bānarjī yāñcyā atyutkrshṭa aitihāsika kādambarīvarūna lihilelẽ - Gurjara, Viṭhṭhala Sītārāma, 1885-1962 (SAMP early 20th-century Indian books project, 1916)
Based on Śaśāṅka, Bengali novel, by Rakhal Das Banerji, 1885-1930.